1976
DOI: 10.2307/2258782
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Six Grassland Herbs in Microsites with Different Water Contents

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…A more exciting possibility is that the extreme sensitivity of seeds to their environment allows individuals to achieve diversified germination strategies even in apparently homogeneous environments. Experimental studies have shown that germination is substantially influenced by the microtopography of the soil surface (Oomes & Elberse 1976) and seed orientation (Sheldon 1974), and recent work has shown that more than 30 per cent of the variation in the timing of germination is related to microgradients even within apparently homogeneous growth chambers (Simons & Johnston 2006).…”
Section: The Canonical Example: Seed Dormancy In Annual Plantsmentioning
confidence: 99%
“…A more exciting possibility is that the extreme sensitivity of seeds to their environment allows individuals to achieve diversified germination strategies even in apparently homogeneous environments. Experimental studies have shown that germination is substantially influenced by the microtopography of the soil surface (Oomes & Elberse 1976) and seed orientation (Sheldon 1974), and recent work has shown that more than 30 per cent of the variation in the timing of germination is related to microgradients even within apparently homogeneous growth chambers (Simons & Johnston 2006).…”
Section: The Canonical Example: Seed Dormancy In Annual Plantsmentioning
confidence: 99%
“…Treatments with more microtopographical relief (soil covered with clods or rocks) had greater germination and root growth of chicory plants, Cichorium intybus, than sites with smooth surfaces or with a litter layer (Smith & Capelle, 1992). Furthermore, sufficient water in the soil is essential for seed germination (Oomes & Elberse, 1976), especially in arid environments, and texture of the soil surface may affect both water infiltration and retention (Gutterman, 1993;Kigel, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Silvertown 1980Silvertown , 1981Fenner 1987;Masuda & Washitani 1990). Furthermore, the canopy structure of the vegetation, which determines both light penetration to the soil surface and microclimate, seems to be an important determinant of the onset of germination and the subsequent fate of seedlings (Oomes & Elberse 1976;Verkaar et al 1983;Fenner 1985;Goldberg 1987). Germination characteristics could therefore play an important role in determining the occurrence of plant species.…”
Section: Introductionmentioning
confidence: 99%